2009
DOI: 10.1590/s0102-86502009000500014
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, manometric and profilometric evaluation after surgery for Hirschsprung's disease: comparison between the modified Duhamel and the transanal rectosigmoidectomy techniques

Abstract: PURPOSE: To evaluate fecal continence, anorectal manometry (AM) and profilometry (P), in patients operated for congenital megacolon, using either the modified Duhamel technique (MDT) or the modified transanal rectosigmoidectomy (MTR) technique. METHODS: 42 patients were evaluated clinically and via AM and P, for postoperative control. The resting, coughing, voluntary contraction, maintained voluntary contraction and perianal stimulation pressures were investigated. The rectosphincteric reflex was tested and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(48 citation statements)
references
References 14 publications
1
38
0
Order By: Relevance
“…This compares favorably with the rates of up to 38% that have been reported in series after Duhamel, Soave, and Swenson procedures. 5,14,[41][42][43][44][45] The estimated prevalences for fecal incontinence after these procedures have ranged between 13% and 17%, 41-43 7% and 34%, and 21% and 29%, 42,46 respectively, with a notion of some improvement in symptoms over time. 5,14,42,43 Although our assessment showed that fecal control following TEPT was initially inferior to controls during childhood, by adulthood, these problems can largely be expected to resolve.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This compares favorably with the rates of up to 38% that have been reported in series after Duhamel, Soave, and Swenson procedures. 5,14,[41][42][43][44][45] The estimated prevalences for fecal incontinence after these procedures have ranged between 13% and 17%, 41-43 7% and 34%, and 21% and 29%, 42,46 respectively, with a notion of some improvement in symptoms over time. 5,14,42,43 Although our assessment showed that fecal control following TEPT was initially inferior to controls during childhood, by adulthood, these problems can largely be expected to resolve.…”
Section: Discussionmentioning
confidence: 99%
“…The reported rates for enterocolitis have ranged from 1% to 39% for Duhamel operation, 14,42,44 6% to 23% for Soave procedure, 23,42 25% to 28% for Swenson and Boley procedures 47 over follow-up periods ranging from 0.5 to 29 years. Although our study suggested that up to 54% of patients may experience at least 1 episode of enterocolitis after TEPT and 21% may experience !4 episodes, these reflect the results of a detailed cumulative enquiry and a long follow-up period of up to 32 years.…”
Section: Discussionmentioning
confidence: 99%
“…Six studies 16,[18][19][20][21][22] were given four to six stars corresponding to a moderate risk of bias, and only one study 17 was given eight stars corresponding to a low risk of bias. Methodological weaknesses common to all studies included inadequate selection of both operative groups as all seven articles [16][17][18][19][20][21][22] were retrospective cohort studies. Demographic features and follow-up descriptions varied between studies (►Table 1).…”
Section: Study Qualitymentioning
confidence: 99%
“…Demographic features and follow-up descriptions varied between studies (►Table 1). Three studies [20][21][22] did not report duration of follow-up. In one study, 18 duration of follow up was too short for some of the outcomes to be accurately assessed, and another study 19 did not explain the large number of subjects that missed follow-up.…”
Section: Study Qualitymentioning
confidence: 99%
See 1 more Smart Citation